(untitled) (Al-Academy, 2022)
Forecasting has become common process and reality. Since man has found multiple forms of simple predictive predictions, fruitful predictive results have emerged, such as weather forecasting or trading on stock exchange. The research was organized by defining the problem, which was manifested by the question:(What is the prediction in global logo design methods?)The aim of the research: (revealing design prediction in the methods of global logos). The theoretical framework was: (the concept of prediction in the design of global logos), (methods of global logos), (types of prediction) and then were attached to indicators, results and conclusions, including:- The color value of international logos came with human needs: a need that modern design schools call for her.The suggestions are:Emphasis on academic studies global logos, as they are advisory principles and values from which the designer sets out to achieve his global logos